Marine mammals : evolutionary biology - Berta, Annalisa; Sumich, James L.; Kovacs, Kit M., 1956- (London, UK : Elsevier, Academic Press, 2015)
Marine Mammals: Evolutionary Biology, Third Edition is a succinct, yet comprehensive text devoted to the systematics, evolution, morphology, ecology, physiology, and behavior of marine mammals. Earlier editions of this valuable work are considered required reading for all marine biologists concerned with marine mammals, and this text continues that tradition of excellence with updated citations and an expansion of nearly every chapter that includes full color photographs and distribution maps.
INTRODUCTION -- Phylogeny, Taxonomy, and Classification -- Pinniped Evolution and Systematics -- Cetacean Evolution and Systematics -- Sirenians and Other Marine Mammals: Evolution and Systematics -- Evolution and Geography -- Integumentary and Sensory Systems -- Musculoskeletal System and Locomotion -- Energetics -- Respiration and Diving Physiology -- Sound Production for Communication, Echolocation, and Prey Capture -- Diet, Foraging Structures, and Strategies -- Reproductive Structures, Strategies, and Patterns -- Population Structure and Dynamics -- Exploitation and Conservation.
Includes bibliographical references and index.
Print version record.
Keywords: Marine mammals; Marine mammals -- Evolution; NATURE -- Animals -- Mammals; SCIENCE -- Life Sciences -- Zoology -- Mammals; Marine mammals; Electronic books